Factor Analysis of Education Students' Interest in Becoming a Teacher - Nurhaliza, Sylvania Arsa; Febriantina, Susan; Maulida, Ervina (Politeknik Assalaam Surakarta, 2025)
The purpose of this research is to determine how the teaching skills practice experience (praktik keterampilan mengajar or PKM) and perception of teacher welfare being affect the interest in becoming a teacher among education students in Faculty of Economics and Business, Universitas Negeri Jakarta, through self-efficacy as a mediating variable. This research uses a quantitative method with a purposive sampling technique to collect data from 162 respondents. Data analysis uses the Structural Equation Modelling (SEM) based on Partial Least Square (PLS) with SmartPLS v4.1.0.9 and employs a Likert scale. The research found that: (1) PKM experience has a positive significant effect on interest in becoming a teacher, (2) PKM experience has a positive significant effect on self-efficacy, (3) Perception of teacher welfare has a positive significant effect on interest in becoming a teacher, (4) Perception of teacher welfare has a positive significant effect on self-efficacy, (5) Self-efficacy has a positive significant effect on interest in becoming a teacher, (6) Self-efficacy plays a mediating role in the influence of PKM experience on interest in becoming a teacher, and (7) Self- efficacy plays a mediating role in the influence of perception of teacher welfare on interest in becoming a teacher.